Condiciones laborales y desempeño de los colaboradores del Gobierno Regional de Loreto Sede Central 2025 - Da Silva Solis, Jorge Luis (2025)
The objective of this study was to determine the relationship between working conditions and the performance of employees at the Loreto Regional Government Headquarters 2025. The methodology was basic, descriptive correlational, and non-experimental. The population consisted of 206 administrative employees. The findings revealed that working conditions were rated as average by 25%, as the workplace temperature was rarely comfortable throughout the workday. However, the lighting in the work area occasionally allowed employees to work comfortably and efficiently. Performance was average at 27%, as employees were sometimes encouraged to propose innovative ideas, had autonomy to make decisions related to their tasks, and experimented with new ways to perform their work more efficiently. Finally, a strong, positive, and statistically significant correlation was found between working conditions and job performance (Rho=0.734; p=0.000). Likewise, a positive and significant relationship was observed between the different dimensions evaluated. Environmental conditions had a coefficient of 0.625, material conditions reached 0.512, social conditions registered 0.478, and finally, time conditions obtained a value of 0.640, all with a significance level of 0.000. These results demonstrated that each of the dimensions analyzed maintained a direct, moderate, and statistically significant relationship with job performance, thus confirming the validity of the research hypotheses.